2018
DOI: 10.1088/1361-6382/aad7f5
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of wavefront errors and jitter in the LISA interferometer: far-field propagation

Abstract: The Laser Interferometer Space Antenna (LISA) is a gravitational wave detector, which aims to detect 10−20 strains in the frequency range from 0.1 mHz to 0.1 Hz. It is a constellation of three spacecrafts, an equilateral triangle with side length of m, where interferometry monitors the spacecraft distances. Aberrations and jitter of the wavefront sent by a spacecraft to the next combine to cause a measurement noise. The paper investigates analytically this coupling, including beam clipping and far-field propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 18 publications
7
43
0
Order By: Relevance
“…However, owing to the large dispersion, a wavefront quality at least equal to λ/20 might be necessary. These results extend and complement our investigation of how the measured spacecraft distance is coupled to the transmitter jitter [6] and open the way to a full start-to-end analysis of the phase noise.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, owing to the large dispersion, a wavefront quality at least equal to λ/20 might be necessary. These results extend and complement our investigation of how the measured spacecraft distance is coupled to the transmitter jitter [6] and open the way to a full start-to-end analysis of the phase noise.…”
Section: Discussionsupporting
confidence: 73%
“…Aberrations and jitter of the wavefront sent by a spacecraft to the next cause a measurement noise. In a previous paper, we investigated the propagation of the wavefront aberrations and the noise of the measured distance originated by the coupling of the aberrations with the transmitter jitter [6]. We found that the sensitivity to the jitter increases from 0.02 pm/nrad to 0.28 pm/nrad when the optical quality of the transmitted wavefront decreases from λ/40 to λ/10.…”
Section: Introductionmentioning
confidence: 97%
“…We can also compare our order of magnitude calculations with the estimates given by Sasso et al [7]. Their estimate, given by their table 3, is δL=0.07 pm/nrad for an amplitude of Zernike of λ/20.…”
Section: 2supporting
confidence: 59%
“…Consequently, wavefront error, as discussed in this article, contributes only to a part of the total tilt-to-length coupling for LISA. The subject of wavefront errors and beam jitter in the LISA optical system has, of course, been the subject of other studies [7,9]. For many years this has been recognized as an important problem for LISA [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation